A prospective study of aspirin use and the risk of gastrointestinal bleeding in men. - Edward S Huang (Public Library of Science (PLoS), 2010)
Background and aims Data regarding the influence of dose and duration of aspirin use on risk of gastrointestinal bleeding are conflicting. Methods We conducted a prospective cohort study of 32,989 men enrolled in the Health Professionals Follow-up Study (HPFS) in 1994 who provided biennial aspirin data. We estimated relative risk of major gastrointestinal bleeding requiring hospitalization or a blood transfusion. Results During 14 years of follow-up, 707 men reported an episode of major gastrointestinal bleeding over 377,231 person-years. After adjusting for risk factors, regular aspirin use (≥2 times/week) had a multivariate relative risk (RR) of gastrointestinal bleeding of 1.32 (95% confidence interval [CI], 1.12-1.55) compared to non-regular use. The association was particularly evident for upper gastrointestinal bleeding (multivariate RR, 1.49; 95% CI, 1.16-1.92). Compared to men who denied any aspirin use, multivariate RRs of upper gastrointestinal bleeding were 1.05 (95% CI 0.71-1.52) for men who used 0.5-1.5 standard tablets/week, 1.31 (95% CI 0.88-1.95) for 2-5 aspirin/week, 1.63 (95% CI, 1.15-2.32) for 6-14 aspirin/week and 2.40 (95% CI, 1.10-5.22) for >14 aspirin/week (P(trend)<0.001). The relative risk also appeared to be dose-dependent among short-term users <5 years; P(trend)<.001) and long-term users (≥5 years; P(trend) = 0.015). In contrast, after controlling for dose, increasing duration of use did not appear to be associated with risk (P(trend) = 0.749). Conclusions Regular aspirin use increases the risk of gastrointestinal bleeding, especially from the upper tract. However, risk of bleeding appears to be more strongly related to dose than to duration of use. Risk of bleeding should be minimized by using the lowest effective dose among short-term and long-term aspirin users.